ARGUMENTATION FOR THE ELABORATION OF THE GUIDE "METHODOLOGICAL HIGHLIGHTS FOR VOCALISTS. PROFESSIONAL-APPLIED PHYSICAL TRAINING AND MENTAL TRAINING". ITS CONTENT AND STRUCTURE - Blîndu Adela (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
This article presents the argumentation for the elaboration of the guide for vocal soloists, which appeared on the background of the creation of a teaching-learning-evaluation unit, for ensuring the necessary consistency, continuity and logical coherence of the content of the Canto discipline. The elaboration of the guide aimed the current and strategic state of scientific research in the field, the creation of skills regarding mental training and the means of PAPT (professional-applied physical training), intended for vocal soloist students.